The Relationship of VAT Rate and Revenues in the Case of Informality - Fikri R. Arrachman; Riatu M. Qibthiyyah (Economics and Finance in Indonesia, 2018)
This study explored relationship between tax rate and revenues in the case of VAT, one of few type of consumption taxes that is considered to be a broad-based tax. Based on a larger set of countries - in comparison to previous studies, this study shows VAT rate has an inverted U-shaped relationship to VAT revenues, confirming the Laffer Curve theory. Exploring further on the effect of informality to maximum VAT rate, we found that higher informality will reduce government flexibility in its effort to increase tax rate. Furthermore, openness has significant and positive effect on VAT revenues performance, and tax administration capacity may also play role on improving VAT revenues performance.